The Spatial Analysis and Dispersal of the Greater Wax Moth (Galleria Mellonella L.?) in Apiaries of Some Central and Southren Iraqi Provinces. (NTU Journal of Agriculture and Veterinary Science, 2025)
This study was an attempt to investigate the prevalence of the greater wax worm, Galleria ?mellonella L., in some provinces of central and southern Iraq Study period from 23\11\2023 to 22\11\2024( Babylon, Karbala, ?Wasit, Qadisiyah, Maysan and Basra). The survey results showed that The pest prevalence was varied in the ?provinces, as the highest infection percentage   in Basra province was reached 73.33%, and ?the lowest in Maysan province reached 10.67%. It is significant to mention that Maysan ?province was also distinguished by having strong hives at a percentage   of 81.7%, while ?Basra had the lowest level of strong hives ? at 30.3%. The methods of controlling the insect ?also was differed in the provinces that were subject to the study. The effective methods of ?controlling the pest that proved their worth in reducing the numbers of the pest and ?eliminating it were burning frames  and dusting frames , and also ?dusting warehouses with dusting discs every two weeks. Besides, the method of freezing ?frames  for two days is a very successful method for eliminating the different insect roles of ?the pest. Daily follow-up is also one of the crucial practices for early detection of the pest, ?whether in the apiary or the storehouse, to take appropriate measures at the beginning of ?the insect’s activity and before it spreads in the apiary and storehouse.?